Cevaplar

2013-02-04T13:37:40+02:00

4sin .sin .sin sin 3
3 3
x x x x
    π π
    + + =
   
2)
2
4cos .cos .cos cos3
3 3
x x x x
    π π
− + + =    
   
3) cotx-2cot2x=tanx
4)
6 6 4 4 2
sin cos 2sin cos sin 0 x x x x x + − − + =
5)
6 6 2 2
sin cos 3sin cos 1 x x x x + + =
6)
2 2 2 2
cot cos cot .cos x x x x − =
7)
( )
( )
2
2 2
2
1 cos .cos sin sin
cos cos
x y x y
x y
− − =

8)
2 2
sin .tan cos cot 2sin .cos
tan cot
x x x x x x
x x
+ + =
+
9) ( ) ( )
4 4 6 6
3 sin cos 2 sin cos 1 x x x x + − + =
10)
tan tan
tan .tan
cot cot
x y
x y
x y
+
=
+
11)
6 6 4 2 4
sin cos cos sin 2sin 0 x x x x x + − + − =
12)
2 2
2 2
tan 2 tan
tan 3 .tan
1 tan 2 .tan
x x
x x
x x

=

13)
2
1 tan 1 sin 2
1 tan 1 sin 2
x x
x x
  + +
  =
  − −
14) tan( ) tan( ) 2 tan 2
4 4
x x x
π π
+ − − =
15) Sin(a+b).cos(a+c)-cos(a+b).sin(a+c)=sin(b-c)
16) cot tan 2 cos 2 cot 2 ( )
2 2
a a
− = + ec a a
17)
tan sec 1
tan sec
tan 1
x x
x x
x cecx
+ −
= +
− +
18)
1 cos sin
tan
1 cos sin 2
x x x
x x
+ −
=
− −
19)
1 1
2sec
sec tan sec tan
x
x x x x
+ =
+ −
20)
1 sin 1 sin
4 tan .sec
1 sin 1 sin
x x
x x
x x
+ −
− =
− +
21)
3 3
sin cos
1 sin .cos
sin cos
x x
x x
x x
+
= −
+
22) (sinx-tanx).(cosx-cotx)=(cosx-1).(sinx-1)
23)
2 2
sec .cos (tan cot ) sec cos x ecx x x x

0